Recognition of Sulfides Zones in Marble Mine Through Comparative Analysis of Electrical Tomography Arrangements - Moreira, César Augusto [UNESP]; dos Santos, Evandro Gomes; Ilha, Lenon Melo; Paes, Renata [UNESP] (Springer Nature, 2019)
This paper involves the use of Induced Polarization method combined with the geological reconnaissance of sulfite rich zones from the comparative analysis of the Dipole–dipole, Schlumberger and Wenner tomographic arrays. The study area comprises a marble mine with metandesites in dykes, sills, and a system of fractures, with enrichment of iron and copper, particularly costly and difficult to explore and study using traditional means of drilling and sampling. In this context, 5 lines of electrical tomography were performed in the three geoelectrical sites previously mentioned. The geophysical data enabled the production of 2D inversion models, later incorporated into 3D visualization models. The correlation between the geological information and the 3D models indicated the characterization of zones with sulfites, with chargeability values over 10 mV/V, and areas without sulfides by values of 1 mV/V. The Dipole–dipole array presented confusing results and anomalous areas displaced regarding the real position. Schlumberger array allowed the correlation between zone with disseminated sulfides and the zone without sulfide mineralization, although it was not possible to identify sulfides in joints and fractures. Wenner arrangement provided a direct correlation of all sulfide and waste zones, possibly due to the horizontal structure of propagation of the electrical and potential fields along the metandesite.
Keywords: 3D modeling; chargeability; dipole; Schlumberger; Sulfides; Wenner